A New Formula for Estimating the Threshold Wind Speed for Snow Movement. (10th November 2017) - He, Siwei; Ohara, Noriaki
Abstract: Threshold wind speed for snow movement is one of the most important parameters describing the wind‐transport snow process. A majority of previous studies used empirical and constant threshold wind speeds while the variations of atmosphere condition and snow age seem to greatly affect the snow settlement process. This study tested the hypothesis that the threshold wind speed for snow transport increases as deposition time passed since last snowfall by introducing a new formula of the threshold wind speed for snow movement. It was theoretically derived based on the sintering process modeling and the moment balance of a snow particle. Through this formula, the influences of snow particle size, temperature, and deposition time on the threshold wind speed were explicitly taken into consideration. However, two empirical parameters in the sintering process modeling remained in the new formula, and they were determined by a calibration‐validation procedure using the field observed snow flux data. The snow flux and meteorological data collected at the ISAW stations (http://www.iav.ch ) including large number of snow transport events during five winter seasons were used to test this formula. It was shown that the new formula qualitatively described the threshold wind speed required for the incipient motion of snow under various conditions in the natural environment of the Alps. Key Points: A physically based formula for the calculation of threshold wind speed for snow movement is derived The threshold wind speed was formulated as a function of snow deposition time as well as temperature The proposed formula is validated using the long‐term observed snow flux data